The effect of customer satisfaction on customer loyalty in the motor industry - Ahasanul Haque, Lim Ka Bian,; Wok, Saoda; Tarofder, Arun Kumar (Opción, 2019)
This study aims to determine the effects of three exogenous variables, namely, service quality, price fairness and Shari’ah compliance on customer loyalty through customer satisfaction as the mediator. Applying the theory of customer satisfaction, a structural equation model was developed and tested on 322 motor Takaful participants from the Klang Valley, Malaysia. The findings suggest that customer satisfaction partially mediates the effects of Shari’ah compliance and price fairness on customer loyalty. In conclusion, participants of motor Takaful are not concerned about the service quality; they are mainly influenced by the price fairness and Shari’ah compliance of the products /services.